Sektor Industri Pengelompokkan Dan Perusahaan Negara Di Kecamatan Ngoro Kabupaten Mojokerto - Rezzylina Dwi Akhirulyati; Andrew Ari Fardana; Muhammad Yasin (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This study aims to determine the environmental impact and natural damage from the production activities of the industrial sector grouping the areas of Ngoro District, Mojokerto Regency for public health in managing environmental cases of alleged waste pollution and natural damage in Mojokerto Regency. The method in this study uses a qualitative approach through observational data collection techniques and also uses a Systematic Literature Review (SLR) approach. According to (Kitchenham & Charter, 2007) SLR is the process of identifying, evaluating, and interpreting all research evidence to answer certain research questions. The results showed that grouping industrial production activities had an impact on the provision of jobs and also infrastructure development in Ngoro Subdistrict and also had an impact on the environment such as waste that was disposed of polluting the watershed and causing fish to die due to contamination of the waste content and polluted residents' well water. In handling these impacts, it is expected that industrial companies in Ngoro can carry out routine monitoring and evaluation activities to see developments in environmental and community conditions, in this case the implementation of policies related to handling the impacts of industrial production activities carried out by companies for public health, especially around Ngoro District, Mojokerto Regency.